2013
DOI: 10.1002/acr.21818
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a multidisciplinary fibromyalgia treatment adapted for women with low educational levels: A randomized controlled trial

Abstract: Objective. Multidisciplinary treatments of fibromyalgia (FM) have demonstrated efficacy. Nevertheless, they have been criticized for not maintaining their benefits and for not being studied for specific populations. Our objectives were to determine the efficacy of a multidisciplinary treatment for FM adapted for patients with low educational levels and to determine the maintenance of its therapeutic benefits during a long-term followup period. Methods. Inclusion criteria consisted of female sex, a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 38 publications
2
36
0
2
Order By: Relevance
“…We note that our findings are in accord with those of other studies that have also reported no improvement in anxiety and depressive symptoms . On the other hand, other researchers have found significant improvements in psychological distress , anxiety and depression . Overall, it seems that having anxiety and/or depressive symptoms does not prevent FM patients from improving in other respects, such as the impact of FM on HRQoL, as observed in our study and others .…”
Section: Discussionsupporting
confidence: 92%
“…We note that our findings are in accord with those of other studies that have also reported no improvement in anxiety and depressive symptoms . On the other hand, other researchers have found significant improvements in psychological distress , anxiety and depression . Overall, it seems that having anxiety and/or depressive symptoms does not prevent FM patients from improving in other respects, such as the impact of FM on HRQoL, as observed in our study and others .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, functional impact based on FIQ scores showed a significant improvement of 20%, which exceeds the amount needed to represent clinically important improvement (Bennett et al, ). This is similar to the previously reported FIQ improvements with drug and non‐drug treatment of about 26% (Castel, et al, ; Clauw et al, ). When directly rating typical functional activities and ADLs, significant improvements were seen in personal care, daily homemaking chores and occupation.…”
Section: Discussionsupporting
confidence: 92%
“…A large, 15‐week randomized trial with milnacipran 100–200 mg reported a mean VAS pain severity reduction from 65 by about 16 points ( p < 0.05) and a Fibromyalgia Impact Questionnaire (FIQ; range 0–100) improvement of 16 points from a baseline score of 62 ( p ≤ 0.01) (Clauw et al, ). Multidisciplinary outpatient treatment (12–24 sessions over 6–12 weeks) has also been shown in randomized studies to reduce pain and fibromyalgia impact significantly (Castel et al, ; Cedraschi et al, ). Pain relief with multidisciplinary care is also typically modest.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide range of conditions investigated, and various outcome measures used, it is difficult to draw any consistent conclusions about the nature of the benefit from MDT working reported. However, where a positive effect was noted, generally sustained improvement in pain severity (Casanueva-Fernandez et al, 2012;Castel et al, 2013), sustained improvement in skills for managing health (Castel et al, 2013), improved emotional and psychological well-being (Castel et al, 2013;Lemstra and Olszynski, 2005) and reduction in inflammatory disease activity (Vliet Vlieland, 1996) were cited as key benefits from MDT involvement. For patients with scleroderma, improvement in pain was not observed, although specific improvements in grip strength and psychological wellbeing were noted (Schouffoer et al, 2011a(Schouffoer et al, , 2011b.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the management of rheumatoid arthritis typically referenced a significant contribution from doctors, nurses, physiotherapists, occupational therapists and podiatrists [Hagel et al, ; Hennell and Luqmani, ; Lambert et al, ; Li et al, ; MacKay et al, ; National Institute for Clinical Excellence (NICE), ; Stewart and Land, ; Taal et al, ; Vliet Vlieland and Hazes, ; Vliet Vlieland et al, ]. Conversely, the management of fibromyalgia typically referenced significant contribution from doctors, physiotherapists, social workers, psychologists and occupational therapists (Carville et al, ; Casanueva‐Fernandez et al, ; Castel et al, ; Manes et al, 2012; Hauser et al, ; Kroese et al, ; Lemstra and Olszynski, ; Sarzi‐Puttini et al, ; van Eijk‐Hustings et al, ). Therefore, while MDT working within rheumatology appears to be beneficial, overall it would appear that the MDT needs to be specifically tailored to suit differing conditions in order to achieve this.…”
Section: Discussionmentioning
confidence: 99%